The Role of FTO Risk Haplotype in Overweight/Obesity and Lipid Parameters-Results From the Central China Population Study - Meiwei Ning; Lin Chen; Yuxue Wang; Aohong Xu; Rong Zeng; Huan Zhang; Boda Wang; Xiang Liu (International Journal of Endocrinology)
Conclusions: There is a linkage imbalance between rs9939609 and rs17817449 in a Central China general population cohort, which also reflected the influence of FTO gene on the risk of overweight/obesity and total cholesterol (TC), triglyceride (TG), and high-density lipoprotein (HDL) disorders. The new findings could provide new clues to predict obesity and metabolic diseases.